Mr. Tony is full of baloney! - Gutman, Dan.; Paillot, Jim (New York : Harper, 2010)
The After School Kids' Care director wants to get into The Guiness Book of World Records, and A. J. and the gang jump in to help him.
My mom's big nose -- Deal or no deal -- Mr. Tony is weird -- Pizza and pogo-juggling -- The sequel to Halloween -- The land of no toilets -- My genius idea -- The biggest pizza in the world -- The greatest day of my life -- Pizza toppings -- A happy ending.
Accelerated Reader
edited hb 2015-06-16
Keywords: Schools -- Fiction; World records -- Fiction; Humorous stories; School-age child care -- Juvenile fiction; World records -- Juvenile fiction